GC-MS ANALYSIS OF METHANOLIC STEM EXTRACT OF GYNOCHTHODES RIDSDALEI, RAZAFIM AND B. BREMER, AN ENDEMIC, ENDANGERED MEDICINAL PLANT OF SOUTHERN WESTERN GHATS - Nair, Renji R.; Gangaprasad, A. (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present research study was undertaken to determine the presence of bioactive components present in the methanolic stem extract of Gynochthodes ridsdalei using Gas Chromatography–Mass Spectrometry (GC-MS) analysis. Methods: the Fresh stem of Gynochthodes ridsdalei collected from the forest areas of Ponmudi region of Thiruvananthapuram district of Kerala state, India was used. The mass spectrum GC-MS of the crude methanolic extract was estimated using the database of National Institute of Standard and Technology (NIST). Results: The active principles with their retention time, peak area, molecular formula, molecular weight, structure and category of the compound were predicted. The analysis revealed the presence of 52 bioactive components. Most of the identified compounds are basically biological important. The components were identified by comparing their retention time and peak area with that of literature and by interpretation of mass spectra. The phyto components screened were of biological importance. Some of them were sterols, anthraquinones, vitamins etc Conclusion: The result reveals the existence of various bioactive compounds and validates the earlier reports of therapeutic importance of the plant. Gynochthodes ridsdalei is recommended as a plant of phytochemical and pharmaceutical importance